2005
DOI: 10.1261/rna.2660805
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and regulatory elements defining constitutive splicing and different modes of alternative splicing in human and mouse

Abstract: Alternative splicing is a major contributor to genomic complexity, disease, and development. Previous studies have captured some of the characteristics that distinguish alternative splicing from constitutive splicing. However, most published work only focuses on skipped exons and/or a single species. Here we take advantage of the highly curated data in the MAASE database (see related paper in this issue) to analyze features that characterize different modes of splicing. Our analysis confirms previous observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 45 publications
8
68
1
1
Order By: Relevance
“…Besides phylogenetic conservation, the strength of the splice sites and the exon/intron architecture (defined in Materials and Methods) has a high impact on the prediction quality of the code. As previously reported (Stamm et al 2000;Clark and Thanaraj 2002;Zheng et al 2005), constitutive splice sites are stronger than alternative splice sites. While constitutive exons in our data sets showed an average combined MES of both splice sites of 17.06, rarely included cassette exons only showed a combined average MES of 13.71.…”
Section: Information Gainsupporting
confidence: 81%
“…Besides phylogenetic conservation, the strength of the splice sites and the exon/intron architecture (defined in Materials and Methods) has a high impact on the prediction quality of the code. As previously reported (Stamm et al 2000;Clark and Thanaraj 2002;Zheng et al 2005), constitutive splice sites are stronger than alternative splice sites. While constitutive exons in our data sets showed an average combined MES of both splice sites of 17.06, rarely included cassette exons only showed a combined average MES of 13.71.…”
Section: Information Gainsupporting
confidence: 81%
“…We also examined whether our results could be explained by splice site strength, which has been previously reported to be lower in minor-form exons than in majorform and constitutive exons (Itoh et al 2004;Baek and Green 2005;Zheng et al 2005). The scatterplot of maxent splice site score versus intron length (Fig.…”
Section: Analysis Of Gc Content Splice Site Strength and Intron Conmentioning
confidence: 88%
“…Upstream or downstream introns <120 nt were excluded. For each upstream or downstream intron, the first and last 50 nt were excluded, since previous studies have shown that patterns of alternative splicing can strongly affect sequence conservation in these flanking intronic regions Kaufmann et al 2004;Baek and Green 2005;Xing and Lee 2005;Zheng et al 2005;Sugnet et al 2006). The clipped intron regions were then queried against the UCSC hg17_multiz17way multigenome alignment (using the software package Pygr, http://bioinformatics.…”
Section: Data Analysesmentioning
confidence: 99%
“…Alternative splicing is a deviation from this preferred sequence where certain exons are skipped resulting in various forms of mature mRNA. Weaker splicing signals at alternative splice sites, shorter exon length or higher sequence conservation surrounding orthologous alternative exons influence the exons that are ultimately included in the mature mRNA (5). This process is mediated by a dynamic and flexible macromolecular machine, the spliceosome, which works in a synergistic and antistatic manner (as explained below) (6,7).…”
Section: Introductionmentioning
confidence: 99%